SOCIAL SECURITY AS A COMPONENT OF THE ECONOMIC SECURITY OF UKRAINE: STATE AND PROSPECTS - NYZHNYK, Viкtor; PRYSTUPA, Mykola (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article defines socio-economic determinants that characterize social security and characteristic features of social security and social protection of Ukraine. The existing social threats and limited economic opportunities in the aspect of social security are studied. In the current realities, it is necessary to determine the priority parameters of social and economic security, which will allow reducing economic restrictions on the social development of the country. The social goals of the concept of sustainable development of society are characterized, the implementation of which is of great importance in the conditions of globalization changes and the choice of the European integration direction of development. Strengthening the relationship between social and economic security of the country requires substantiation of a number of social indicators, influencing factors, systematization of risks and threats. The relationship between social security and the formation of economic security at the level of the state, region, city, and personal security is presented, which is manifested in institutional and economic factors, risks, threats, and parameters for assessing the social component in the formation of economic security. Taking into account the fact that social security is a functionally important component in the formation of economic security of Ukraine for solving the tasks and problematic aspects in all sectors of the economy, the stages of the process of developing social programs are revealed. Proposed directions for improving social security as a component of the economic security of Ukraine. Ensuring stable economic development is impossible without social stability, and therefore the development of national security depends on the effective formation of economic security, all its components, including social security. A comprehensive approach to solving the issues of social and economic security formation of Ukraine is the basis of its social and economic development, social consolidation in the conditions of choosing the European integration vector and the foundations of social development and economic security.
Keywords: social security; economic security; social protection of the population; socio-economic threats